Effects of Transport Stress (Duration and Density) on the Physiological Conditions of Marbled Rockfish (Sebastiscus marmoratus, Cuvier 1829) Juveniles and Water Quality - Jiahao Wang; Kaida Xu; Xinyi Chen; Haoxue Wang; Zhe Li (Fishes)
Live transportation is a critical component of fish farming and hatchery release. To optimize hatchery-release techniques and improve the survival rate of marbled rockfish (Sebastiscus marmoratus, Cuvier 1829) juveniles, the effects of varying transport durations (2, 4, 6, and 8 h) and densities (60, 90, 120, and 150 kg m−3) on the physiological indicators of the fish and water quality were investigated under controlled laboratory conditions. We found that as transport duration and density increased, water quality significantly deteriorated, with ammonia nitrogen levels rising and dissolved oxygen content and pH levels decreasing. Physiological indicators including levels of lactate, cortisol, and malondialdehyde and activities of superoxide dismutase, alkaline phosphatase, and glutamate oxaloacetate transaminase notably increased, indicating that the fish experienced heightened stress during transport. Additionally, the mortality rate of juveniles increased significantly with increasing density and transport duration. The high mortality rate might be associated with sustained elevated cortisol levels and liver damage. Our results are helpful for determining the optimal transport conditions for S. marmoratus juveniles and also provide valuable insights for improving transport techniques for other aquatic animal species.